STRATEGI PELAYANAN PUBLIK DALAM MENDUKUNG ADAPTASI KEBIASAAN BARU DITINAJU DARI UU NO. 25 TAHUN 2009 - Wesley Liano Hutasoit (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Public services are provided by public service providers. Public service providers, hereinafter referred to as State Administrators. The essence of the implementation of public services is to provide public welfare services. The research objective was to see the public service strategy in supporting New Habit Adaptation (AKB) in terms of Law No.25 of 2009. The study used a qualitative approach with descriptive analysis methods of library research type. Library research using library data learning methods, reading, and taking notes and processing research materials. Discussion of research results, articles, news obtained through the literature, and official government agency source websites and sources relevant to the research. How to work in the Covid-19 era gave birth to new disciplines while the process of getting used to it in public services was needed. The new disciplinary process tends to access technology online. Directly based on a new adaptation pattern which becomes an obligation. Social phenomena seem irrational when isolating themselves at home, the government gathers, the streets are closed, the industry stops operating, schools use bold media, and public services are carried out online. In reality, this condition occurs in all countries. The transition period is a moment to transform and reset old public services to new ones. Regeneration of service updates is important to do considering the era of information technology today.